Perceptions of Spanish nurses on economic crisis and the impacts on health care system - Helena Maria Scherlowski Leal David; José Ramón Martínez-Riera; Sonia Acioli; Maria Fernanda de Lima da Costa (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to analyze the perceptions of Spanish nurses regarding the country's economic crisis situation, and its impacts on nursing work, health system and population's health. Methods: qualitative approach, with data collection using an internet-based questionnaire and individual in-depth interviews. Data were analyzed according to Thematic-Categorical Content Analysis, supported by Historical and Dialectical Materialism perspective. Results: the categories produced discuss themes as: cutbacks in health care and the consequences of workforce non-replacement and work overload; salary impact; care model changes; negative impacts on population health. The impact on population health and work was discussed, especially regarding vulnerable groups, as well as in assistance model reconfiguration, reinforcing the biomedical and assistance perspective.